Selective Oxidative Degradation of Organic Pollutants by Singlet Oxygen-Mediated Photosensitization: Tin Porphyrin versus C-60 Aminofullerene Systems - Kim, Heechan; Kim, Wooyul; Mackeyev, Yuri; Lee, Gi-Seon; Kim, Hee-Joon; Tachikawa, Takashi; Hong, Seokwon; Lee, Sanghyup; Kim, Jungbae; Wilson, Lon J.; Majima, Tetsuro; Alvarez, Pedro J. J.; et al. (American Chemical Society, 2012)
This study evaluates the potential application of tin porphyrin- and C-60 aminofullerene-derivatized silica (SnP/silica and aminoC(60)/silica) as O-1(2) generating systems for photochemical degradation of organic pollutants. Photosensitized O-1(2) production with SnP/silica, which was faster than with aminoC(60)/silica, effectively oxidized a variety of pharmaceuticals. Significant degradation of pharmaceuticals in the presence of the 400-nm UV cutoff filter corroborated visible light activation of both photosensitizers. Whereas the efficacy of aminoC(60)/silica for O-1(2) production drastically decreased under irradiation with lambda > 550 nm, Q-band absorption caused negligible loss of the photosensitizing activity of SnP/silica in the long wavelength region. Faster destruction of phenolates by SnP/silica and aminoC60/silica under alkaline pH conditions further implicated O-1(2) involvement in the oxidative degradation. Direct charge transfer mediated by SO, which was inferred from nanosecond laser flash photolysis, induced significant degradation of neutral phenols under high power light irradiation. Self-sensitized destruction caused gradual activity loss of SnP/silica in reuse tests unlike aminoC(60)/silica. The kinetic comparison of SnP/silica and TiO2 photocatalyst in real wastewater effluents showed that photosensitized singlet oxygenation of pharmaceuticals was still efficiently achieved in the presence of background organic matters, while significant interference was observed for photocatalyzed oxidation involving non-selective OH radical.